APPLICATIONS OF SPACERS MADE WITH DOUBLE BAR RASCHEL MACHINE - DÍAZ-GARCÍA Pablo; BONET-ARACIL Mariles; BOU-BELDA Eva; MONTAVA Ignacio (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2016)
Nowadays, textile technologies develop to adapt their different techniques for creating new products for the different sectors of application every day. Particularly, warp knitted fabrics and warp-knitting technology have applications in all different groups of technical textiles. It could be the most applied technique, the most versatile technology to develop new textile products for the new textile market. Warp knitted fabrics play the most important role among the technical textile fabrics. This technology is used in different product groups such as mobile textiles (car seat covers, dashboard cover), industrial textiles (composites), medical textiles (anti-decubitus blankets), sports textiles and foundation garments (bra cups, pads for swimwear). This study presents some examples of the application of this technology in some markets Within the market of technical textile, medical textile has an increasing relevance and knitted fabrics and knitting technology, at the same time, play a very important role in the fields of technical and medical textiles. Studies have demonstrated that knitted structures possess excellent mechanical properties and can promote more effective regenerative medicine, tissue repair, ligament, tendon cartilage, reconstruction, etc. The aim of this paper is to present different possibilities of textiles developed with this kind of structures, to present different alternatives, different examples of products obtained with this kind of textile structure combined with the correct kind of textile fiber. In this kind of technology, double-bar Raschel machines used for producing three-dimensional textiles, spacers, play an important role.